Inside the Mind of the Entrepreneur Cognition, Personality Traits, Intention, and Gender Behavior (Contributions to Management Science,, 2018)
This book connects entrepreneurship and psychology research by focusing on the personality dimensions of entrepreneurs, entrepreneurial cognition, entrepreneurial leadership, and gender behavior. It features state of the art interdisciplinary research offering a unified perspective on entrepreneurial psychology. Individual chapters address advances related to entrepreneurial intentions, complexity management, personality psychology, intrapreneurial behavior, entrepreneurial communities and demographic changes, among others. Laboratory experiments that study entrepreneurial behavior round out the coverage.